The Political Ecology of the Modern Peasant : Calculation and Community - Anderson, Leslie (Leslie E.) (Book collections on Project MUSE., 1994)
"Why do some peasants rebel while others are quiescent? This comparative study of six peasant villages in Nicaragua and Costa Rica asserts a theory of 'political ecology' by which individual and community interests sometimes reach beyond the village boundary and combine in the selection of political choices. Strong theoretical approach, rich contextual backdrop, sound methodology. Major contribution"--Handbook of Latin American Studies, v. 57.